The Big Five, Learning Goals, Exam Preparedness, and Preference for Flipped Classroom Teaching: Evidence from a Large Psychology Undergraduate Cohort. (March 2017) - Lyons, Minna; Limniou, Maria; Schermbrucker, Ian; Hands, Caroline; Downes, John J.
Previous research has found that the flipped classroom (i.e., learning prior to the lecture, and using the lecture time for consolidating knowledge) increases students' deep learning, and has an association with improved grades. However, not all students benefit equally from flipping the classroom, and there may be important individual differences that influence preference for different teaching styles. In the present study, undergraduate Psychology students ( n  = 200) answered questions about exam preparedness, learning goals, preference for the traditional or flipped classroom, and the Big Five of personality. We found that preference for the flipped classroom had a significant, positive association with agreeableness and the mastery goal. Preference for the traditional lecture was predicted by beliefs about exam preparedness. The results are discussed with a reference to the Big Five paradigm in the context of learning and teaching.